Salmonid Jumping and Playing: Potential Cultural and Welfare Implications - Robert Fagen (Animals, 2017)
Salmonids of several species and other fishes can jump into the air from the water. This behavior has been used in net pen culture applications to control parasitic sea lice. The reasons that salmonids jump remain a topic for speculation. Research on these behaviors has focused on Atlantic salmon in net pen culture in Northwest Europe. Jumping in salmonids is a heterogeneous behavioral category with diverse functional outcomes. Additional research is needed from broad perspectives spanning indigenous and institutional science, cultural wisdom, and ethological direct observation. In theory and in practice, it is interesting that some salmonid jumping behavior may be a form of play.